The role of Parliament in shaping foreign policy - Evaldas Nekrašas (Politologija, 1998)
The article deals critically with the doctrine according to which in the process of shaping and implementing foreign policy, the executive branch of the government has many advantages over the legislative and should prevail over it. Foreign policy making in Sweden, United Kingdom, and United States is examined, both on the basis of the results of field research conducted by the author himself and on the findings of other authors. According to the author, the widely made assumption that in all countries foreign policy is almost the exclusive domain of the executive is not correct. In some countries, Parliament plays a relatively important role in this area.